TI_GERICHTE 72.2013.68 vom 12. November 2013 , Riciclaggio di denaro, falsità in documenti (artt. 251 CP, 305bis CP) - TI Tribunale d'appello (2013)
Riciclaggio di denaro, falsità in documenti (artt. 251 CP, 305bis CP)